Optimasi Proses Pengolahan Oli Bekas Pada Suhu Outlet Furnace Melalui Proses Distilasi Vakum - Dyan Wahyu Tri Utomo; Sebastian Bagasswari; Sinar Perbawani Abrina Anggraini; Kun Aussieanita Mediaswanti (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
Oil is a non-renewable natural resource derived from petroleum. PT ALP Petro Industry is an industry that processes used oil back into new oil using vacuum distillation. The purpose of this study is to determine the outlet furnace temperature in optimizing each oil product by using the main pump, furnace, distillation column, exchanger, and tank. This research used vacuum distillation methodology by determining the temperature of the outlet furnace so that it gets the optimal oil product yield. This study uses a fixed variable used oil of raw material with a maximum water content of 0.1% and the flow rate of feed 4000 kg/h and uses a variable temperature of 376°C, 377°C, 378° C, 379°C, 380°C in the furnace outlet. The results showed that at outlet furnace temperature 376°C the yield of SLF oil products was 8.4%, LLF 35.0%, and HLF 16.6%. At temperature 377°C the SLF product yield was 12.2%, LLF 38.0%, and HLF 14.4%. At temperature 378°C the yield of SLF products was 14.9%, LLF was 40.8%, and HLF was 11.5%. At temperature 379°C the yield of SLF products was 15.6%, LLF 42.0%, and HLF 11.4%. At temperature 380°C the yield of SLF products was 16.3%, LLF 43.5%, and HLF 11.0%. Different outlet furnace temperatures produce different oil product yields because each fraction has different boiling points. The higher the outlet furnace temperature, the lower the HLF fraction oil product yield, and the higher LLF and SLF oil product yield. The lower the outlet furnace temperature, the higher the HLF oil product yield, and the lower LLF and SLF oil product yield.